Assessment of Governance and Corruption in the Pharmaceutical Sector : Lessons Learned from Low and Middle Income Countries - Diack, Aissatou (World Bank, Washington, DC, 2013)
Pharmaceuticals are a critical input for the health sector. At the same time, the drug business sustains many individual and corporate livelihoods and produces handsome returns for those involved in the trade. Good governance is critical for the sector to maximize returns for public health and minimize risks for patients from ineffective or contaminated drugs. Given the large financial volume of the market, the potential for corruption is significant. Vulnerable points are those at which decisions about market access and purchasing are made. This includes institutional functions such as licensing, inclusion into formularies and public procurement as well as the individual prescriber, who selects drugs for a specific patient. Given the political and institutional resistance against more transparency from the beneficiaries of the status quo, assessment of governance and corruption in the sector is not a straightforward exercise. The authors developed a more indirect approach that relies on a broader assessment of the functioning of the sector and detection of patterns that suggest governance or management problems. From a developmental perspective, the focus is on reducing the impact of bad governance (high drug prices, stock-outs, bad quality of drugs in circulation, irrational use of drugs) rather than identifying the actors and bringing them to justice. Even if the governance level cannot be touched due to political resistance, it may be possible to address the problem from a technical or management angle. For example, electronic procurement platforms and inventory management systems make manipulation more difficult and allow for a faster discovery of irregularities. The assessment framework was applied in eight countries, with adjustments based on client demand and political viability. In most cases, a follow-up after the assessment could be documented, showing that the data provided had relevance and impact in the national policy dialogue. Three of the eight countries signed up to a longer term program to increase transparency in the sector (medicines transparency alliance), others initiated specific projects to address issues that were presented as a result of the initial assessment. In summary, the authors work could demonstrate that it is possible to effectively address pharmaceutical governance issues in the context of a broader sector assessment an approach that may face less political resistance than an inquiry based on a "governance and corruption" labeled instrument.